Speech Regarding Clean Indoor Air (Tufts Archival Research Center, 2007)
Illegible/Difficult to Read; Handwritten; Speech by unidentified tobacco control proponent discussing the failure of Proposition 5 in California. Emphasizes the role of public opinion and support for the successful passage of any tobacco legislation. Explains that the role of legislation is not to attack smokers because they would feel that their civil rights would be threatened. Mentions the fact that non-smokers should not be forced to breathe secondhand smoke. Encourages the audience that it is possible to pass useful tobacco control legislation in the state of California.